Aqueous Extract of Carica papaya Leaves Improves Hyperglycemia, Hyperalgesia, and Oxidative Stress in Streptozocin-induced Diabetic Peripheral Neuropathy in Male Wistar Rats (African Journal of Biomedical Research, 2023)
Aqueous extract of Carica papaya leaves was investigated for its acclaimed neuroprotective activity in streptozotocin-induced diabetic peripheral neuropathy in rats. Twenty male, Wistar rats weighing between 120 & 170g were randomly assigned into four groups of five animals each. Rats in group 1 were normal, healthy rats that received normal saline 1.0ml/kg b. w. Those in group 2 (diabetic untreated) received normal saline 1.0ml/kg b. w., group 3 was treated with pregabalin 0.71mg/kg b. w. and group 4 received the aqueous leaf extract of Carica papaya 200mg/kg b. w. Plasma glucose concentration, thermal and mechanical allodynia, and biochemical biomarkers in the brain [malondialdehyde (MDA) and nitric oxide (NO)]; nerve [brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF)]; and serum [superoxide dismutase (SOD) and glutathione (GSH)] were assessed. The results showed that the Carica papaya leaf-treated (group 4) rats had a significant fall in the plasma glucose level (p˂0.0001); higher pain threshold on ice cold and von Frey tests (p